Detection of nanoflare-heated plasma in the solar corona by the FOXSI-2 sounding rocket. (November 2017) - Ishikawa, Shin-nosuke; Glesener, Lindsay; Krucker, Säm; Christe, Steven; Buitrago-Casas, Juan Camilo; Narukage, Noriyuki; Vievering, Juliana
Abstract The processes that heat the solar and stellar coronae to several million kelvins, compared with the much cooler photosphere (5, 800 K for the Sun), are still not well known1 . One proposed mechanism is heating via a large number of small, unresolved, impulsive heating events called nanoflares2 . Each event would heat and cool quickly, and the average effect would be a broad range of temperatures including a small amount of extremely hot plasma. However, detecting these faint, hot traces in the presence of brighter, cooler emission is observationally challenging. Here we present hard X-ray data from the second flight of the Focusing Optics X-ray Solar Imager (FOXSI-2), which detected emission above 7 keV from an active region of the Sun with no obvious individual X-ray flare emission. Through differential emission measure computations, we ascribe this emission to plasma heated above 10 MK, providing evidence for the existence of solar nanoflares. The quantitative evaluation of the hot plasma strongly constrains the coronal heating models. The authors detect hard X-ray emission produced by plasma heated at ≥10 million kelvin from a quiescent active region of the Sun, providing clear observational evidence of plasma heating by nanoflares, and hinting at their important role in coronal heating.